The Impact of Wear and Lift-Off on Coronal Plane Alignment in TKA and Implications to Future Constrained Revision: A Retrieval Study - Vandekerckhove, Pieter-Jan T.K.; Teeter, Matthew G.; Naudie, Douglas D.R.; Howard, James L.; MacDonald, Steven J.; Lanting, Brent A. (The Journal of arthroplasty, 2015)
Current discussion exists whether to position a total knee arthroplasty (TKA) in slight undercorrection in varus osteoarthritis. The goal of this study was to analyse the effect of wear and lateral lift-off in primary TKA on coronal plane alignment and the implication to future constrained revision TKA. Seventy-six retrieved tibial inserts were analysed for the ratio of wear (RW), lateral lift-off and implications for future constrained revision surgery according to the coronal plane alignment. The RW significantly affects the coronal plane alignment in TKA. Progressive wear and lateral lift-off were seen with progressive varus alignment. However, there was no difference in constrained revision between mild varus and moderate varus aligned TKAs.